2021
DOI: 10.1038/s41370-021-00327-3
|View full text |Cite
|
Sign up to set email alerts
|

Personal care product use among diverse women in California: Taking Stock Study

Abstract: Background: Personal care product use may contribute to elevated body burdens of consumer product chemicals among women of color; however, racial/ethnic differences in product use has been understudied. Community-engaged research can support the recruitment of diverse participants. Objective: To document personal care product use among a diverse group of women (aged 18-34 years) living in California. Methods: Through a community-academic partnership, we surveyed 357 women in California about product use inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…Cumulative exposure to the same or similarly acting chemicals from frequent use of multiple products may have additive effects and result in higher-than-expected exposures. A recent survey in California found that women used a median of 8, and up to 30, personal care products daily [ 45 ]. We found a total of 37 CoCs listed on labels of 546 products, and up to 10 CoCs listed on a single product.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative exposure to the same or similarly acting chemicals from frequent use of multiple products may have additive effects and result in higher-than-expected exposures. A recent survey in California found that women used a median of 8, and up to 30, personal care products daily [ 45 ]. We found a total of 37 CoCs listed on labels of 546 products, and up to 10 CoCs listed on a single product.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed an increased risk of PTB in women that frequently used hair oils, which contain EDCs, during the last trimester of pregnancy [147]. Interestingly, Black women are more likely than other races to report using hair oil [148]. Although data are limited concerning the potential role of EDCs contributing to the known racial disparity in the risk of PTB, some important inferences can be drawn.…”
Section: Premature Birthmentioning
confidence: 76%
“…These race and ethnicity trends are consistent with the results of previous studies. 6,7,11 Though we did not collect data on specific brands or product constituents, prior work has shown that the products marketed to Black/African American women tend to have higher levels of potentially harmful chemicals, 5,6,14,29 further augmenting the exposure burden for this demographic group. 7 Women were fairly consistent in their reported use of both products, and reliability improved further when more general classifications of ever versus never use were compared.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][11][12][13][14] Studies of the long-term health effects of feminine hygiene product use are inherently based on observational rather than experimental data. Some previous studies have described patterns of use, 6,11,12,15,16 but none of these have considered use across the life course, which is often a more relevant metric for understanding the health impacts of feminine hygiene product use on chronic disease outcomes. However, if historic use cannot be accurately recalled, measurement error can bias effect estimates, especially if recall reliability differs by outcome status.…”
mentioning
confidence: 99%